LNRRIL6, a novel long noncoding RNA, protects colorectal cancer cells by activating the IL‐6–STAT3 pathway - Jiaxing Wang; Junfeng Zhou; Caiyun Jiang; Jing Zheng; Hiroki Namba; Pan Chi; Tetsuya Asakawa (Molecular Oncology)
Long noncoding RNAs (lncRNAs) are emerging as critical regulators of cancer. There is a comparable number of lncRNAs to protein‐coding genes, but the expression patterns, functions, and molecular mechanisms of most lncRNAs in colorectal cancer (CRC) remain unclear. In this study, we report the identification of a novel lncRNA, named long noncoding RNA regulating IL‐6 transcription (LNRRIL6), which is upregulated in CRC tissues and cell lines. Increased LNRRIL6 expression is associated with aggressive clinicopathological characteristics and poor prognosis of CRC patients. Functional experiments showed that enhanced expression of LNRRIL6 promotes CRC cell proliferation and survival in vitro and CRC tumor growth in vivo. Conversely, depletion of LNRRIL6 inhibits CRC cell proliferation and survival in vitro and CRC tumor growth in vivo. Mechanistically, we revealed that LNRRIL6 physically binds to the IL‐6 promoter, thereby increasing IL‐6 transcription, inducing IL‐6 autocrine signaling, and activating the IL‐6/STAT3 pathway. The expression of IL‐6 is positively associated with that of LNRRIL6 in CRC tissues. Blocking the IL‐6/STAT3 pathway using the FDA‐approved IL‐6‐receptor antagonist antibody, tocilizumab, abolished the oncogenic role of LNRRIL6 in CRC. Taken together, these findings identify a novel lncRNA, LNRRIL6, that promotes CRC cell survival through activation of the IL‐6/STAT3 pathway and suggest that LNRRIL6 may be a potential prognostic biomarker and therapeutic target for CRC.